Customer relationship management: Modern aspects of information technology application - Soldić-Aleksić Jasna; Krasavac-Chroneos Biljana (Marketing (Beograd. 1991), 2008)
The concept of Customer Relationship Management has emerged around the maxim on the essential importance of the customers for business success of the company. The vital role in the concept development is assigned to an employment of the various information communication technologies: in the scope of operational CRM that is the application of Internet technologies, web browsers, e-mails, POS terminals, call centers; on the other side, analytical CRM involves activities such as data mining, web mining, click stream analysis etc. Modern tendencies in the development of information-communication technologies have generated new communication models between company and its customers, therefore companies are not only focused on the products and services, but also on the communication channels and techniques with customers. On that ground many companies are accepting and using new tools belonging to the web 2.0 technologies which have produced the new CRM model - CRM 2.0.